Toward a Link Between IT Determinants and Their Adoption: Empirical Analysis Based on Practicing Chartered Accountants - Thottoli, Mohammed Muneerali (Indonesian Journal of Sustainability Accounting and Management, 2022)
The main objective of this study is to investigate the association of information technology (IT) training, IT perceived benefits, and IT benefits with IT adoption among practicing Chartered Accountants (CAs). The study then explained the implications of IT adoption and evaluated the relationship between IT training, IT perceived usefulness, and IT usefulness to practicing accountants. Employing a quantitative approach, a series of questionnaires were culled out by making the necessary adjustments to the available items. A total of 88 qualified CAs practicing in Kerala were analyzed. As part of the data analysis, the study used Structural Equation Modeling–Partial Least Squares (SEM–PLS) software. The results of the study have shown a positive significant relationship between two determinants, namely, IT training and IT perceived usefulness, but IT usefulness has no relationship with IT adoption by practicing CAs. This study added to the literature by analyzing IT determinants and the adoption of auditing software among practicing auditors.